Effects of recombinant growth hormone (GH) replacement and psychomotor and cognitive stimulation in the neurodevelopment of GH-deficient (GHD) children with cerebral palsy: a pilot study - Devesa J; Alonso B; Casteleiro N; Couto P; Castañón B; Zas E; Reimunde P (Dove Medical Press, 2011)
Jesús Devesa1,2, Begoña Alonso1, Nerea Casteleiro1, Paula Couto1, Beatriz Castañón1, Eva Zas1, Pedro Reimunde1,21Medical Center “Proyecto Foltra”, Cacheiras (Teo), A Coruña, Spain; 2Department of Physiology, School of Medicine, University of Santiago de Compostela, SpainAbstract: Cerebral palsy (CP) is the main cause of physical disability in childhood and is an important health issue that has a strong socioeconomic impact. There is no effective treatment for CP and therapeutic approaches report only partial benefits for affected people. In this study we assessed the effects of growth hormone (GH) treatment combined with psychomotor and cognitive stimulation in the neurodevelopment of children with CP and GH deficiency (GHD). The study was carried out in 11 patients (7 boys and 4 girls; 4.12 ± 1.31 years) with GHD and CP who were treated with recombinant GH (rGH) and psychomotor and cognitive stimulation during 2 months. Battelle Developmental Inventory Screening Test (BDIST) was performed 2 months before commencing GH treatment, just before commencing GH administration, and after 2 months of combined treatment involving GH and cognitive stimulation. Psychomotor and cognitive status did not change during the period in which only cognitive stimulation was performed; however, significant improvements in personal and social skills, adaptive behavior, gross motor skills and total psychomotor abilities, receptive and total communication, cognitive skills and in the total score of the test (P < 0.01), and in fine motor skills and expressive communication (P < 0.02) were observed after the combined treatment period. Therefore, GH replacement together with psychomotor and cognitive stimulation seem to be useful for the appropriate neurodevelopment of children with GHD and CP.Keywords: growth hormone, cerebral palsy, cognitive functions, Battelle’s test, neurodevelopment